Práticas integrativas e complementares para controle de náuseas e vômitos em gestantes: revisão sistemática - Nassif, Melissa Santos (2021)
The pregnancy process is accompanied by several biopsychosocial changes, including nausea and vomiting, which are often associated with negative feelings, in addition to physical impacts and on maternal quality of life. In this scenario, integrative and complementary practices are inserted as a potential treatment to control these symptoms in this population. The aim of this review is to synthesize the evidence available in the literature on the effectiveness of integrative and complementary practices in the treatment of nausea and vomiting in pregnant women. This systematic review included only randomized controlled trials that evaluated the effects of integrative and complementary practices versus placebo, routine treatment or pharmacological intervention to control nausea and vomiting in healthy pregnant women. Outcomes of interest were related to nausea and vomiting and possible adverse effects arising from the applied intervention. The search for articles was performed in 11 databases/databases from December 2020 to January 2021. There were no restrictions regarding the year of publication or the language of the manuscripts. The texts were evaluated in three steps: reading the titles, reading the abstracts and reading in full. Subsequently, data of interest were selected and extracted, which were evaluated for the risk of bias. The entire process was carried out by two ind ependent reviewers and a third was available to resolve disagreements. This study was carried out based on the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis and had its protocol registered in the International prospective register of systematic reviews CRD42020221570. The final sample consisted of 31 articles, divided into three categories: aromatherapy, herbal medicine and acupuncture. Aromatherapy with lemon essential oil, the use of ginger capsules and acupressure at the CS6 point were the most frequent interventions among those that proved effective. Less than half of the studies reported adverse effects, with mild and transient symptoms predominating. Most articles were classified as “some concern” in assessing the risk of bias. It was not possible to conduct the meta-analysis due to the heterogeneity of the data. It is expected that the results of this systematic review will support further research on the aforementioned PICS and later favor the implementation of integrative and complementary practices in the protocols for the control of gestational nausea and vomiting, in order to facilitate the insertion of these tools of easy administration, low cost and effective, and that, above all, can encourage nursing to explore this field, which is within its competence.